Oesophagectomy without gastric Drainage Procedure - Jan, Sharif Ullah (Journal of Postgraduate Medical Institute, 2011)
To know the outcome of oesophagectomy without gastric drainage procedure. This is an observational study, which was conducted at cardiothoracic unit LRH, Peshawar form may 2002 to may 2004. the study comprised of patients subjected to subtotal oesophagectomy, where stomach was used as replacing conduit and anastomosis was done in neck with no gastric drainage procedure. Oesophagestomy without gastric drainage is successful procedure as it does not require revision surgery for gastric stasis.